2020
DOI: 10.5114/jcb.2020.98110
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of post-implant dosimetrics between intraoperatively built custom-linked seeds and loose seeds by sector analysis at 24 hours and 1 month for localized prostate cancer

Abstract: Purpose: To compare post-implant dosimetrics between intraoperatively built custom-linked (IBCL) seeds and loose seeds (LS) at 24 hours and 1 month by sector analysis, and to evaluate the effect of IBCL seeds with regard to change in dosimetric parameters, in patients with prostate cancer treated with brachytherapy. Material and methods: Consecutive patients treated for localized prostate cancer who received definitive brachytherapy between March 2013 and October 2017 were retrospectively analyzed. Prostate V … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…However, they worsen over time and it is important to know the long-term efficacy. In addition, there are different techniques with seeds, with prior planning or with real-time, and various seed construction systems, with variable implant dosimetry quality, including loose, linked, and intra-operatively built custom-linked seeds [ 4 ]. A good technique and optimized dosimetry are able to improve the results at five years, while comparing two groups of similar patients [ 5 ].…”
Section: Purposementioning
confidence: 99%
“…However, they worsen over time and it is important to know the long-term efficacy. In addition, there are different techniques with seeds, with prior planning or with real-time, and various seed construction systems, with variable implant dosimetry quality, including loose, linked, and intra-operatively built custom-linked seeds [ 4 ]. A good technique and optimized dosimetry are able to improve the results at five years, while comparing two groups of similar patients [ 5 ].…”
Section: Purposementioning
confidence: 99%
“…Such results may be more favorable to the formulation of a preoperative implantation plan to control post-implantation radiation damage. In addition, it is also necessary to include D100, V150, and V200, because D100 can reflect the dose in the peripheral area of the tumor, and V150 and V200 can reflect the volume of the high dose within the tumor target ( 5 , 6 ). In our recent study ( 6 ), we found that the faster the tumor shrank, the more likely the 125 I seeds were to gather centrally, which might lead to the local ultra-high dose region, thereby causing radiation damage to surrounding normal tissues.…”
mentioning
confidence: 99%